GENDER EQUALITY IMPACT ON FOREIGN DIRECT INVESTMENT GROWTH OF ASEAN COUNTRIES - Vernanda Fairuz; Muhammad Findi Alexandi; Yeti Lis Purnamadewi (AFEBI Economic and Finance Review, 2019)
ASEAN become one of the main destination location for Foreign Direct Investment (FDI) however its FDI growth showed a declining trend. On the other hand, gender equality of this region keep progressing over time and surpassed the global average gender equality index. This paper examined the effect of gender equality on the growth of foreign direct investment inflows using static panel model for eight ASEAN countries for 2010-2016 period. Our result showed that gender equality could boost the FDI inflow growth through the increase of labor force participation and tertiary education. Labor force participation able to enhance the effort of boosting FDI growth through the macroeconomic channel such as GDP growth, infrastructure, inflation, interest rate and exchange rate.